Effects of γ irradiation on the electric conduction of PZT ceramic system - Zachariasz, R.; Rymarczyk, J.; Ilczuk, J. (Archives of Acoustics, 2006)
In the work, the results of investigations of the electric conduction σ of the PZT ceramics with the two following compositions: Pb_0.94Sr_0.06(Zr_0.5Ti_0.5)O_3 + 0.25% wt. Cr_2O_3 (hard material) and (Pb_0.9Ba_0.1)(Zr_0.53Ti_0.47)O_3 + 1.67% wt. Nb_2O_5 (soft material), are presented. The “soft” ceramics are characterized by high electric values (ε^T_33/ε_0 > 1300 (in room temperature), d_31 = 120 · 10^−12 C/N) and electromechanical coupling coefficient (k_p > 0.5). Due to good parameters it is used in electromechanical transducers of low frequency. The “hard” PZT ceramics, which are used in resonators, filters and ultrasound transducers are characterized by the following parameters: ε^T_33/ε_0 > 900 (in room temperature), d_31 = 65· 10^−12 C/N and electromechanical coupling coefficient k_p > 0.35. The temperature dependences of the electric conduction σ for all samples before and after γ irradiation with dose of 20 kGy were performed. The activation energy E_a was calculated on the basis of the ln σ = f(1/T) dependences.